Activity of fosfomycin/colistin combinations against planktonic and biofilm Gram-negative pathogens. (5th May 2022) - Boncompagni, Selene Rebecca; Micieli, Maria; Di Maggio, Tiziana; Aiezza, Noemi; Antonelli, Alberto; Giani, Tommaso; Padoani, Gloria; Vailati, Silvia; Pallecchi, Lucia; Rossolini, Gian Maria
Abstract: Objectives: To investigate the in vitro activity of fosfomycin, colistin and combinations thereof against planktonic and biofilm cultures of Gram-negative pathogens, mostly showing MDR phenotypes, at concentrations achievable via inhalation of aerosolized drugs. Methods: Activity against planktonic cultures was tested by the chequerboard assay with 130 strains, including 52 Pseudomonas aeruginosa, 47 Klebsiella pneumoniae, 19 Escherichia coli, 7 Stenotrophomonas maltophilia and 5 Acinetobacter baumannii . Activity against biofilm cultures was tested by biofilm chequerboard and quantitative antibiofilm assays with a subset of 20 strains. In addition, 10 of these strains were tested in mutant prevention concentration (MPC) assays. Results: Against planktonic cultures, synergism between fosfomycin and colistin was detected with a minority (10%) of strains (eight K. pneumoniae and five P. aeruginosa ), while antagonism was never observed. Synergism between fosfomycin and colistin against biofilms was observed with the majority of tested strains (16/20 in biofilm chequerboard assays, and 18/20 in the quantitative antibiofilm assays), including representatives of each species and regardless of their resistance genotype or phenotype. Furthermore, combination of fosfomycin and colistin was found to significantly reduce the MPC of individual drugs. Conclusions: Fosfomycin and colistin in combination, at concentrations achievable via inhalation of nebulized drugs, showed notable synergy against MDR Gram-negative pathogens grown in biofilm, and were able to reduce the emergence of fosfomycin- and colistin-resistant subpopulations.